PENGARUH TEMPERATUR DAN JUMLAH LINTASAN PEMADATAN TERHADAP DENSITY PERKERASAN ASPHALT CONCRETE WEARING COURSE - Muhammad Fahruddin; Budi Hartanto Susilo (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2018)
Hotmix performance is very dependent on volumetric characteristics and Marshall characteristics, one of the parameters of which is density. Unmet density will affect other Marshall parameters which can also result in early damage to road pavement. This thesis is the result of research in the field and in the laboratory which aims to analyze the effect of temperature at the stage of exposure, and the stage of compaction as well as the number of compaction paths on the density of pavement AC-WC type IVB Asphalt Institute. Research in the field is divided into two categories that are distinguished at the temperature of the exposure to meet the specification requirements and do not meet. The results showed that there was a tendency that the temperature of the dispersion in the range of requirements had a stronger correlation to get the value of the hotmix density according to the requirements compared to the overlay temperature not in the range of requirements. The regression equation model relates the laying temperature (X1), the initial compaction temperature (X2), and the number of compaction paths (X3) to the hotmix density (Y) obtained are: Y = 82,7 + 0,021X1 + 0,033X2 + 0,409X3.